Department B. of the Court of Cassation (1920-1941) - Drakić, Gordana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Department B. of the Court of Cassation was established in 1920 upon decision of the Ministerial Council of the Kingdom of Serbs, Croats and Slovenes. Special Regulation on the Organization of the Department B. of the Belgrade Court of Cassation in Novi Sad was passed on September 17, 1920. Department B. of the Court of Cassation in Novi Sad started operations in February 1921. This judicial body was tasked to adress legal issues, but also to organize legal life in the territory of Vojvodina. In 1930, a special law was passed which prescribed relocation of seat of the Department B. of the Court of Cassation from Novi Sad to Sombor. The Presidency of the Department B. had responsibility to make the necessary arrangements in order to provide the conditions for the transfer of judges, court staff, their families, and also court inventory. However, relocation of the seat of the Department B. of the Court of Cassation wasn’t conducted. In the archives there is no data on the reasons that had contributed to the fact that the law on relocation of the Department B. wasn’t implemented in practice. Establishment and operation of the Department B. of the Court of Cassation in Novi Sad had a great significance for the consolidation of judicial circumstances in the territory of Vojvodina between the two world wars.